Forecasting rice yield under climate scenarios and evaluation of agro-adaption measures for Mekong Basin Region : a simulation study - Agarwal, Anshul; Herath, Srikantha A.; Ranamukhaarachchi, S.L.; Clemente, Roberto S.; Perret, Sylvain Roger; Babel, Mukand Singh; AIT Fellowship; WEM Sponso red Project (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Climate change and global warming pose a significan t threat to agriculture and global food security. This study investigates effects of c limate change on rainfed rice yield and agro adaptation measures to mitigate its impacts us ing CERES-Rice crop growth model. The research has been carried in Ubon Ratchathani, Khon Kaen and RoiEt provinces of Northeast of Thailand. Future climate scenarios for period 2020-29, 2050-59 and 2080- 89 were developed using global climate model ECHAM4 and downscaled using PRECIS regional climate model. The reductions in yield will reach almost 18, 28 an d 24% in the region during 2020s, 2050s and 2080s respectively compared to the averag e yield of years 1997 to 2006. The yield was predicted to decline by 15% for rice cult ivar KDML105 and 5.5% for rice cultivar RD6 with each degree rise in temperature f rom ambient level. On the contrary, increase in yield was observed by 8.7% for KDML105 and 17.45% for RD6 with every 100 ppm rise in CO 2 from ambient level. It was verified that the decrease in yield under fu ture climate scenarios can be mitigated significantly using proper management practices in terms of nutrient management and alternate planting dates. It can save the crops fro m harmful effect of temperature during spikelet sterility. Hybrid rice cultivars having hi gh temperature tolerance will also help to meet the challenges imposed by changed climate s cenarios.
Climate change and global warming pose a significant threat to agriculture and global food security. This study investigates effects of climate change on rainfed rice yield and agro adaptation measures to mitigate its impacts using the CERES-Rice crop growth model. The model was calibrated using the secondary data for the field experiments conducted in Ubon Ratchathani, Khon Kaen and RoiEt provinces in Northeast region of Thailand. Future climate scenarios for the period 2020-29, 2050-59 and 2080-89 were developed using the global climate model, ECHAM4 and downscaled using the regional climate model, PRECIS, The reduction in yield will reach almost 18, 28 and 24% in the region during 2020s, 2050s and 2080s, respectively, compared to the average yield of years 1997-2006. The yield is predicted to decline by 15% for rice cultivar KDML105 and 5.5% for rice cultivar RD6 with each degree rise in temperature from the ambient level. On the contrary, an increase in yield is expected by 8.7% for KDML105 and 17.45% for RD6 with every 100 ppm rise in CO2 from the ambient level. It is found that the decrease in yield under future climate scenarios can be mitigated significantly using proper management practices in terms of nutrient management and altering planting dates. It can prevent the crop from harmful effect of temperature during spikelet sterility. Hybrid rice cultivars having high temperature tolerance will also help to meet the challenges imposed by changed climate scenarios
A thesis submitted in partial fulfillment of the re quirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2007
Keywords: Rice -- Climatic factors